Effect of acupuncture at the sphenopalatine ganglion for the treatment of moderate to severe seasonal allergic rhinitis: Study protocol for a three-armed randomized controlled trial - Wang, Weiming; Chen, Hui; Gao, Ning; Yu, Shudan; Liao, Jiahua; Wang, Shijie; Gao, Ziqi; Liu, Zhishun (Frontiers in Medicine, 2022)
Introduction: Seasonal allergic rhinitis (SAR) is a major health problem with a relatively high worldwide prevalence that severely limits the quality of life for sufferers. Acupuncture is widely used for SAR treatment in China; however, the evidence on the efficacy of acupuncture at the sphenopalatine ganglion (SPG) for SAR is inconclusive. Therefore, this study aims to investigate the efficacy and safety of acupuncture at the SPG acupoint for the treatment of SAR. Methods and analysis: A total of 120 participants with SAR will be recruited and randomly assigned to the acupuncture group, placebo acupuncture (PA) group, or rescue medication (RM) group with a 1:1:1 allocation ratio. Participants in the acupuncture group and PA group will receive 8 sessions of acupuncture stimulus at the SPG plus RM or 8 sessions of shallow needling at the SPG acupoint plus RM for 4 weeks with a 4-week follow-up in the first year and a 1-week follow-up in the second year. Participants in the RM group will only receive RM throughout the study. The primary outcome is the change from baseline in the average daily combined symptoms and medication score (CSMS) over weeks 1–4. All analysis will be based on an intention-to-treat principle. All statistical tests will be two-sided and a p-value <0.05 will be considered to be statistically significant. Keywords: Acupuncture; Seasonal allergic rhinitis; sphenopalatine ganglion; randomized controlled trial; protocol